Monocarboxylate Transporters MCT1 and MCT4 Regulate Migration and Invasion of Pancreatic Ductal Adenocarcinoma Cells. Issue 7 (August 2016) - Kong, Su Chii; Nøhr-Nielsen, Asbjørn; Zeeberg, Katrine; Reshkin, Stephan Joel; Hoffmann, Else Kay; Novak, Ivana; Pedersen, Stine Falsig
Abstract : Objectives: Novel treatments for pancreatic ductal adenocarcinoma (PDAC) are severely needed. The aim of this work was to explore the roles of H + -lactate monocarboxylate transporters 1 and 4 (MCT1 and MCT4) in PDAC cell migration and invasiveness. Methods: Monocarboxylate transporter expression, localization, activity, and function were explored in human PDAC cells (MIAPaCa-2, Panc-1, BxPC-3, AsPC-1) and normal human pancreatic ductal epithelial (HPDE) cells, by quantitative polymerase chain reaction, immunoblotting, immunocytochemistry, lactate flux, migration, and invasion assays. Results: MCT1 and MCT4 (messenger RNA, protein) were robustly expressed in all PDAC lines, localizing to the plasma membrane. Lactate influx capacity was highest in AsPC-1 cells and lowest in HPDE cells and was inhibited by the MCT inhibitor α-cyano-4-hydroxycinnamate (4-CIN), MCT1/MCT2 inhibitor AR-C155858, or knockdown of MCT1 or MCT4. PDAC cell migration was largely unaffected by MCT1/MCT2 inhibition or MCT1 knockdown but was reduced by 4-CIN and by MCT4 knockdown (BxPC-3). Invasion measured in Boyden chamber (BxPC-3, Panc-1) and spheroid outgrowth (BxPC-3) assays was attenuated by 4-CIN and AR-C155858 and by MCT1 or MCT4 knockdown. Conclusions: Human PDAC cells exhibit robust MCT1 and MCT4 expression and partially MCT1- and MCT4-dependent lactate flux. PDAC cell migration is partially dependent on MCT4; and invasion, on MCT1 and MCT4. Inhibition of MCT1 and MCT4 may have clinical relevance in PDAC. Abstract : Supplemental digital content is available in the text.